Min panjang ujaran dan kemahiran pragmatik kanak-kanak 35 hingga 46 bulan di Kota Bharu, Kelantan - Nur Hanisah, Tukiran (Pusat Pengajian Sains Perubatan, 2010)
This study aimed to investigate the mean length of utterance (MLU) and the two elements of pragmatic skills, i.e the conversational abilities and communicative functions of children in Kota Bharu, Kelantan. A total of 14 children aged 35 to 46 months were recruited in this study. They are subdivided into two groups; first group consisted of those 35- 40 months while another group was 41-46 months. A 30-minutes interaction between the researcher and the subject was recorded by audio and visual in order to evaluate the MLU and pragmatic skills of each subject. The results showed that the MLU of each subjects are lower (mean= 1.95 & 2.45) than Brown's finding (1973); mean= 3.38 & 4.13. However, there is a general increase in the MLU value with age and it was significant (R= 0.918, R.2= 0.843). For pragmatic skills, both age groups have same abilities (p= 0.948 & 0.112).